Pengaruh Penerapan Model Pembelajaran Everyone is A Teacher Here terhadap Hasil Belajar Siswa di SMA Negeri Parakansalak Sukabumi - Nurul Diah Hidayati; Endin Nasrudin; Ahmad Suryadi (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2021)
The purpose of this study intends to determine the reality of the application of the learning model Everyone is a teacher here in the subject of Islamic Religious Education, to determine the reality of student learning outcomes in Islamic Religious Education subjects and to determine the reality of the effect of implementing the learning model Everyone is a teacher here on learning outcomes. students in the subject of Islamic Religious Education. The method used in this research is descriptive method. While the data collection techniques through questionnaires, observation and interviews. Then the data analysis used partial analysis and correlational analysis. The conclusion in this study is that the Islamic religious education learning model using the “everyone is a teacher here” model shows that the learning process through the “everyone is a teacher here” model can be carried out well. Student learning outcomes in the subject of Islamic Religious Education (PAI) with the application of the